Uropathogens Preferrentially Interact with Conditioning Film Components on the Surface of Indwelling Ureteral Stents Rather than Stent Material - Kymora B Scotland; Sonia HY Kung; Ben H Chew; Dirk Lange (Pathogens, 2020)
Despite routine implementation in urology, indwelling ureteral stents pose as a nidus for infection. Conditioning film accumulates on stents, which prime pathogen adhesion, promoting infectious biofilm formation. However, the extent to which conditioning film components play a role in facilitating bacterial adhesion and biofilm formation remains largely unknown. Here, we examined the interaction of previously identified stent-bound conditioning film components (fibrinogen, uromodulin, and albumin) with bacterial uropathogens. Cytoscopically removed stents were incubated with common uropathogens (Escherichia coli, Enterococcus faecalis, and Staphylococcus aureus). Immunofluorescent double staining was performed to study the localization of uropathogens relative to stent-bound conditioning film proteins. Conditioning film components were identified on the external stent surface with some deposition in the inner lumen. Bacteria co-localized with fibrinogen, uromodulin, and albumin, suggesting a potential mechanism for stent-associated infections. Here, we determine strong co-localization between common uropathogenic bacterial species with prominent conditioning film components on ureteral stents. Further functional validation of interactions amongst these uropathogens and conditioning film proteins may enhance clinical management for stent-associated infections and development of improved stent technologies.